Was the 2018 Hokkaido Eastern Iburi Earthquake in Japan Related to Carbon Capture and Storage (CCS)-CO2 Injection? Insights From Geomechanical Analysis - Lei, Xinglin (Frontiers in Earth Science, 2022)
In a recent paper [“Groundwater anomaly related to CCS-CO2 injection and the 2018 Hokkaido Eastern Iburi earthquake in Japan” by Sano et al (2020)], the authors claimed that CO2-enriched fluid may have initially migrated through permeable channels, blocking the fluid flow from the source region, increasing pore pressure in the focal region and triggering a natural earthquake where the brittle crust was already critically stressed. The proposed model is very interesting, but the authors have not shown any quantitative evaluation supporting their conclusion. Here, through geomechanics model analysis, even under extreme conditions, which overestimate the impact of the injection, the impact of the CO2 injection on the Iburi earthquake fault, whether the deep section or shallow part of the fault, is much lower than that caused by Earth tides. In addition, no convincing mechanism exists that would allow fluid channels to heal within a short period of time and block the natural fluid flow along the fault. Therefore, the occurrence of earthquakes was not related to CO2 injection. Geological storage of CO2 is expected to become an effective option for global warming countermeasures, and the assessment of its environmental impact must be carefully conducted.